DOP35 High-fat diet reduces gut microbiota-derived metabolite indole-acetic acid and aggravates colitis. (30th January 2023) - Li, M; Dong, Y; Zhang, K; Ma, J; He, L; Wei, J; Jiang, J; Zhao, Q; Zhao, Q; Cao, H
Abstract: Background: It is widely accepted that high-fat diet (HFD) has been considered as one of the risk factors of inflammatory bowel disease(IBD), while the mechanism is little known. We aimed to examined whether dietary high fat promotes colonic inflammation through modulating gut microbial tryptophan metabolites. Methods: The C57BL/6 female mice were fed with chow diet (12kcal% fat) or HFD (60kcal% fat) for 2 weeks. Fresh fecal samples were collected before administration of 2% DSS. LC-MS/MS analysis was performed to detect fecal microbial tryptophan metabolites. Next, 8-week-old mice were administrated 3-indoleacetic acid (IAA) for 7 days prior to 2.5% DSS treatment. The severity of colitis was assessed and the colonic sections were collected. RNA sequencing was performed to analyze the differential genes in intestinal tissue of mice fed with IAA or not. Real-time PCR and Western blotting were performed to detect the transcription and protein expression of mucin sulfation-related genes. High iron diamine-alcian blue (HID-AB) staining of colon tissues and LS174T cells was used to detect the abundance of sulfated mucin. Additionally, the Chromatin immunoprecipitation (ChIP) sequencing is performed to confirm the binding of aryl hydrocarbon receptor(AHR) to 3'-phosphoadenosine 5'-phosphosulfate (PAPS) synthase 2 (PAPSS2). Results: Short-term HFD increased the susceptibility to colitis of mice. Mice fed with HFD have impaired tryptophan metabolism with remarkable lower level of IAA. IAA supplementation resulted in ameliorative colitis symptoms. Mechanistically, the transcriptome sequencing detected that IAA supplementation enriched the the cytosolic sulfonation pathway and significantly increased the expression of PAPSS2 of colon tissue, a rate-limiting enzyme on the mucin sulfation pathway. Next, in vivo and in vitro experiments verified IAA increased the expression of PAPSS2 and its downstream genes and promoted the mucin sulfation in golgi apparatus of colon through AHR. ChIP sequencing and ChIP-PCR verified IAA can enhance the binding of AHR to the promoter region of PAPSS2, which further promoted the expression of PAPS transporter 2 (PAPST2 or Slc35b3) and ultimately promotes the mucin sulfation. Conclusion: HFD altered the gut microbial tryptophan metabolites and disrupt the protective effect of IAA on the intestinal barrier. IAA could relief colitis through AHR-PAPSS2-PAPST2-mucin sulfation axis, which may present a potential approach for precise prevention and treatment of IBD.